Probiotic Multistrain Treatment May Eradicate Helicobacter pylori from the Stomach of Dyspeptics: A Placebo-Controlled Pilot Study - Rosania, Rosa; Filomena Minenna, Maria; Giorgio, Floriana; Facciorusso, Antonio; De Francesco, Vincenzo; Hassan, Cesare; Panella, Carmine; Ierardi, Enzo (Inflammation & Allergy-Drug Targets (Discontinued), 2012)
Probiotics survive in gastric environment competing with H. pylori. We studied probiotic “multistrain” administration in dyspeptics with H. pylori (placebo-controlled study). Forty patients with H. pylori (urea breath test - UBT - and IgG) were treated for 10 days with a mixture of 8 species of probiotics. Control group represented by 40 positive subjects received placebo. A second UBT and H. pylori stool antigen (HpSA) detection were performed after 1 month. Patients who remained infected were treated with triple therapy undergoing another UBT after 30 days. A second line therapy was administered in remaining positive patients. Statistics: Fisher’s exact probability and Student’s t tests. Thirteen out 40 patients using probiotics became negative, while controls remained positive, irrespectively of the initial UBT delta value. No difference in the eradication rates between the two groups was found (68%-71%). After second line therapy two patients remained positive.Thirteen out 40 patients using probiotics became negative, while controls remained positive, irrespectively of the initial UBT delta value. No difference in the eradication rates between the two groups was found (68%-71%). After second line therapy two patients remained positive. An adequate supplementation with probiotics might eradicate H. pylori.
Keywords: second line therapy